“Thermal Peroxidation” of Dietary Pentapeptides Yields N-Terminal 1,2-Dicarbonyls - Bikaki, Maria; Kuhnert, Nikolai (Frontiers in Nutrition, 2021)
In this contribution we investigate the thermal degradation of dietary relevant pentapeptides. Most unsaturated lipids degrade by the well-known peroxidation mechanism. Here we show a degradation mechanism of peptides analogous to lipid peroxidation, forming a series of novel degradation products with possible toxicological relevance. At elevated temperatures above 180° C pentapeptides with an N-terminal phenylalanine moiety react via a debenzylation to form 1,2-dicabonyl compounds. We propose a radical based reaction mechanism that leads via a common peroxoaminal intermediate to two distinct types of reaction products with a terminal α-1,2 diamide or an α-amide-aldehyde functionality.